Organizational behavior [10th ed.] emerging knowledge, global reality - McShane, Steven L.; Von Glinow, Mary Ann (New York McGraw-Hill, 2024)
Organizational Behavior 10th edition helps everyone make sense of OB and provides the conceptual tools to work more effectively in the workplace. It emphasizes emerging OB knowledge with globally focused, real-world examples and evidence-based literature. This book presents the reality that organizational behavior is not just for managers; it is relevant and valuable to anyone who works in and around organizations. This edition explains how design thinking and agile methodologies are improving creativity and decision making in organizations; how self-concept is a significant determinant of individual behavior, team cohesion, and leadership; how employees increasingly communicate and coordinate through emerging digital channels; how emotions influence employee motivation, attitudes, and decisions; and how global mindset has become an important employee attribute in this increasingly diverse and inclusive interconnected world.
Keywords: Organizational behavior